Raman spectroscopy and X-ray diffraction studies of (GeS₂)₁₀₀₋x(SbSI)x glasses and composites on their basis - Rubish, V.M.; Stefanovich, V.O.; Maryan, V.M.; Mykaylo, O.A.; Shtets, P.P.; Kaynts, D.I.; Yurkin, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The structure and structural changes under the isothermal annealing of (GeS₂)₁₀₀₋x(SbSI)x (0 ≤ x ≤ 90) glasses were investigated by Raman spectroscopy and X-ray diffraction methods. The nanoheterogeneous nature of these glasses structure has been revealed. The matrix of (GeS₂)₁₀₀₋x(SbSI)x glasses is basically built just of binary GeS4, SbS3 and SbI3 structural groups and contains a small amount of molecular fragments with homopolar Ge - Ge and S - S bonds. The phase structure arising in the glass matrix at crystallization corresponds to the structure of crystalline SbSI.